ANTIBACTERIAL EFFECT OF VIRGIN COCONUT OIL ON (ACTINOMYCES SP.) THAT CAUSES DENTAL BLACK STAIN IN CHILDREN - Lavine, Priscilla; Fauziah, Eva; Rizal, Mochamad Fahlevi; Budiardjo, Sarworini Bagio (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: This study aimed to assess the effectiveness of virgin coconut oil (VCO) as a natural antibacterial agent to reduce the viability of the chromogenic bacteria Actinomyces sp., which causes dental black stains. Methods: Actinomyces sp. was isolated from the saliva of a child diagnosed with black stain. Each streak of bacteria was cultured on a selective medium Actinomyces agar and confirmed visually and through a gram staining procedure. Each bacterial culture was exposed to VCO in concentrations of 12.5%, 25%, 50%, and 100%. Afterward, viability testing with a methyl-thiazolyl-tetrazolium assay was conducted, and the results were read using an enzyme-linked immunosorbent assay reader. Results: The reduction of bacterial viability of Actinomyces sp. showed a significant difference between the negative control group and the groups treated with various concentrations of VCO 12.5%, 25%, 50%, and 100%. Conclusion: The minimum concentration of VCO necessary to kill Actinomyces sp. is VCO 12.5%.